Effects of metabolic syndrome on arterial function in different age groups: the Advanced Approach to Arterial Stiffness study - Topouchian, Jirar; Labat, Carlos; Gautier, Sylvie; Bäck, Magnus; Achimastos, Apostolos; Blacher, Jacques; Cwynar, Marcin; de la Sierra, Alejandro; Pall, Denes; Fantin, Francesco; Farkas, Katalin; Garcia-Ortiz, Luis; et al. (Journal of hypertension, 2018)
OBJECTIVE: The aim of the Advanced Approach to Arterial Stiffness study was to compare arterial stiffness measured simultaneously with two different methods in different age groups of middle-aged and older adults with or without metabolic syndrome (MetS). The specific effects of the different MetS components on arterial stiffness were also studied. METHODS: This prospective, multicentre, international study included 2224 patients aged 40 years and older, 1664 with and 560 without MetS. Patients were enrolled in 32 centres from 18 European countries affiliated to the International Society of Vascular Health & Aging. Arterial stiffness was evaluated using the cardio-ankle vascular index (CAVI) and the carotid-femoral pulse wave velocity (CF-PWV) in four prespecified age groups: 40-49, 50-59, 60-74, 75-90 years. In this report, we present the baseline data of this study. RESULTS: Both CF-PWV and CAVI increased with age, with a higher correlation coefficient for CAVI (comparison of coefficients P < 0.001). Age-adjusted and sex-adjusted values of CF-PWV and CAVI were weakly intercorrelated (r = 0.06, P < 0.001). Age-adjusted and sex-adjusted values for CF-PWV but not CAVI were higher in presence of MetS (CF-PWV: 9.57 ± 0.06 vs. 8.65 ± 0.10, P < 0.001; CAVI: 8.34 ± 0.03 vs. 8.29 ± 0.04, P = 0.40; mean ± SEM; MetS vs. no MetS). The absence of an overall effect of MetS on CAVI was related to the heterogeneous effects of the components of MetS on this parameter: CAVI was positively associated with the high glycaemia and high blood pressure components, whereas lacked significant associations with the HDL and triglycerides components while exhibiting a negative association with the overweight component. In contrast, all five MetS components showed positive associations with CF-PWV. CONCLUSION: This large European multicentre study reveals a differential impact of MetS and age on CAVI and CF-PWV and suggests that age may have a more pronounced effect on CAVI, whereas MetS increases CF-PWV but not CAVI. This important finding may be due to heterogeneous effects of MetS components on CAVI. The clinical significance of these original results will be assessed during the longitudinal phase of the study.
Keywords: dospělí; hypertenze; Female; Pulse Wave Analysis; Age Factors; Adult; Dyslipidemias; ženské pohlaví; triglyceridy; Obesity; Metabolic Syndrome; věkové faktory; Triglycerides; lidé; analýza pulzové vlny; tlakový index kotník-paže; Blood Glucose; Ankle Brachial Index; lipoproteiny HDL; tuhost cévní stěny; studie případů a kontrol; hyperglykemie; metabolický syndrom; Aged, 80 and over; krevní tlak; prospektivní studie; Arteries; obezita; Hypertension; Case-Control Studies; Aged; Male; Prospective Studies; Hyperglycemia; dyslipidemie; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Vascular Stiffness; Blood Pressure; krevní glukóza; Middle Aged; arterie; Lipoproteins, HDL; Humans